Comparison of parents' evaluation of developmental status and professional assessment for early detection of developmental disorders in infants born at term with birth asphyxia at Tembisa hospital - Mbuyi, Faustin Kabasele (My University, 2016)
Background: Screening tools that rely on parents’ information are effective tests used in child health to improve developmental outcomes. The PEDS combined questionnaires are designed for the overall developmental assessment of children aged 0-8 years and facilitate early intervention programs. Aim: This study aimed to compare the PEDS combined and health professionals ‘developmental assessment as part of routine standard of care in eliciting neurodevelopment deviations in infants born at term with history of birth asphyxia at Tembisa Hospital, a public health care sector in South Africa. Method: The present study is a descriptive cross sectional study. The developmental outcomes from the routine professional assessments were obtained from the review of medical records. Parents were asked to answer the PEDS combined questionnaires when their child was 6-12 months old to elicit developmental milestones in the infants. The comparative analysis was determined using the Kappa coefficient. Results: The study sample included 34 infants and their parents (N=34). The PEDS combined questionnaires found that 7 (21%) infants had variable developmental concerns and unmet milestones, while the review of medical records revealed that 3 (9%) infants had development that was not age appropriate. The overall resulting kappa agreement between the PEDS combined and the routine professional assessment was moderate (K= 0.544, 95% CI 0.170 to 0.917); with the PEDS combined more likely to identify developmental concerns and unmet milestones which included gross motor (K= 0.622), fine motor (K= 0.785), self-help (K= 0.532), socio-emotional (K˂ 0.20) and communication (K˂ 0.20). On the contrary, the routine professional assessment was more likely to identify an infant with other/health concerns (K˂ 0.20). Conclusion: The PEDS combined screening test was more likely to identify more infants at risk of developmental problems. On the other hand, routine professional assessment, used in isolation, presented a risk of under-detection of developmental issues and could result in lack of referral of infants for early intervention. Socio-demographic characteristics did not influence the information provided by parents. If presented with standardised screening questionnaires, all parents can give accurate information about their child.
A research report submission to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Medicine: Child Health and Neurodevelopment 2015